MODERNIZATION OF COLOR- FOUNDRY DEPARTMENTS: MODEM EQUIPMENT, MATERIALS, TECHNOLOGY - A. Ju. Sezonenko; Ju. D. Sezonenko; A. B. Sezonenko (Литьë и металлургия)
There are given some developments of ChP "SAS engineering company'' on modernization of equipment for melting of non-ferrous metals and alloys.